A LEADERPRENEURSHIP TRAINING MODEL FOR ELEMENTARY SCHOOL PRINCIPALS IN THE FRAMEWORK FOR GUARANTING SCHOOL QUALITIES - Johar Permana; D Deni Koswara; Cepi Triatna (Universitas Pendidikan Indonesia, 2010)
Efforts to the quality, assurance of the school level requires the parties directly responsible for the quality of service to stakeholders in education, especially in the service of learning. Principals as school leaders and managers have a role in ensuring the quality of school education, although schools are on limited resources and sources of funds, the principal office must be able to have a dig requirements, lead, empower and open participation of stakeholders effectively. Based on the identification of the primary head of Management Training in 2005 was organized by the Training office in Bandung, that the skills that should be owned by the school with limited resources many schools are in leadership .skills, entrepreneurship (leaderpreneurship). The essence of leadership is the ability leaderpreneurship be based by the entrepreneurial spirit to respond to the demands strategic environment, its limitations and the strengths and challenges into opportunities to achieve toe school. Leaderpreneurship have competency: head of school able to self-reliance aid planning, school quality,, able to organize school activities effectively, implement all activities that have been developed, which has a strong personality, able to communicate ideas / thoughts and school programs, personnel and influence stakeholders to achieve the god of schools, and able to manage financial resources and school in a participatory, transparent and accountable, in order leaderpreneurship development, the researchers created a model for training principals leaderpreneurship both the new and old who have served as a form of quality assurance in schools.